Risk governance through public sector interactive control systems: The intricacies of turning immeasurable uncertainties into manageable risks. Issue 6 (18th August 2022) - Kominis, Georgios; Dudau, Adina; Favotto, Alvise; Gunn, Douglas
IMPACT: Some public services, like children's services, are subject to considerable political sensitivity and undergo regular reforms, but little is known of the micro-processes supporting macro-level regulation and policy-making. This article provides insights into this micro-level of inter-organizational relations by investigating risk governance and negotiation employed by English children's services professionals in their attempt to make sense of the uncertainty in which they operate. Public managers may extract lessons on the role of partnership working in risk identification, measurement and governance. They could also employ the authors' risk typology (organizational risk, professional risk and risk to clients) to manage and absorb uncertainty beyond, as well as within, organizational boundaries. ABSTRACT Drawing on the conceptual distinction between risk and uncertainty, the authors examine the governance of shared risk in public sector partnerships in an area governed by uncertainty. Their case study of a local safeguarding children board (LSCB) reveals differences between risk and uncertainty and ways in which negotiations of LSCB partners' different risk conceptualizations contributes to uncertainty reduction in children's services. The article contributes to both to an understanding of risk and uncertainty management in the public sector and to that of public sector inter-organizational management accounting and control.